Improvement Frequency of Information Access and Anxious, Impact on The High Level of Compliance Protocol Prevention COVID-19 in Nurse Candidates - Muflih, Muflih; Syafitri, Endang Nurul; Adyani, Sang Ayu Made (Jurnal Keperawatan Respati Yogyakarta, 2020)
The spread of the COVID-19 virus which has become a pandemic is thought to cause changes in health behavior in nurse candidates. The purpose of this study is to identify changes in health behavior of nursing students in the form of seeking health information and increasing anxious about the possibility of contracting the virus, which is thought to have an impact on increasing compliance with health behavior. This type of research is an online survey with cross-sectional design. Data collected from nursing students in their late teens were statistically analyzed by the correlation test. The results showed that increasing literacy in seeking information about COVID-19 cases from social media and a fairly high increase in anxious had an impact on increasing compliance with preventing the spread of the virus. However, it was found that exposure to case information did not increase anxious in respondents. The conclusion of this study is the need for increased health literacy to create compliance with the COVID-19 virus prevention protocol at the same time as an increase in anxious.Â